Evaluation of Risk Management Implementation in the Radiotherapy Unit of Grandmed Hospital, Lubuk Pakam, in 2023 - Sumantri, Bambang (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Radiotherapy installations are among the high-risk healthcare service units due to the use of ionizing radiation in cancer treatment. Evaluating the implementation of risk management is essential to ensure the safety of patients, healthcare workers, and the surrounding environment. This study aims to evaluate the extent to which risk management has been implemented in the Radiotherapy Installation at Grandmed Hospital Lubuk Pakam in 2023. A descriptive qualitative method was used through observations, interviews with healthcare personnel, and document analysis of standard operating procedures (SOPs) and incident reports. The results of the study indicate that risk management practices have been implemented, but not yet optimally, particularly in aspects such as incident reporting and regular training. Strengthening the reporting system, continuous training, and internal audits are necessary to improve the effectiveness of risk management in the facility.This study employed a descriptive approach using qualitative methods. Data were collected through in-depth interviews with radiotherapy unit staff, direct observations, and document reviews related to the risk management system. The evaluation was conducted based on the ISO 31000 risk management standard and guidelines from the Nuclear Energy Regulatory Agency (BAPETEN).The evaluation results indicated that most hospitals have implemented the basic components of risk management, such as hazard identification, risk analysis, and risk control. However, it was found that the processes of risk monitoring and evaluation have not been carried out systematically. In addition, not all installations had complete risk documentation or conducted regular training updates.The implementation of risk management in radiotherapy installations is at a promising early stage, but improvements are still needed, particularly in the areas of documentation and the strengthening of safety culture. Strong management commitment and ongoing training are essential to enhance the effectiveness of the risk management system to ensure the safety of both patients and medical personnel